When is a line of inquiry ‘reasonable’? - a focus on digital devices - Horsman, Graeme (Taylor & Francis, 2023)
Many of the inquiries now made by law enforcement into suspected criminal conduct involve the interrogation of digital data generated by those parties subject to an investigation. This data often exists in large quantities where inquiry-irrelevant information is likely to be in abundance. When conducting an investigation that contains digital device/data, an investigatory team in England and Wales is under an obligation to pursue all reasonable lines of inquiry, however, determining ‘reasonableness’ is not straightforward where unfettered access to all available data should not be a default position in all cases and a suspect’s right to privacy respected. This work examines when a line of inquiry is ‘reasonable’ if it involves a digital device, with the ‘reasonable line of inquiry framework’ offered to support investigatory teams to determine this. This approach is designed to support the production of transparent, robust and defensible decisions regarding the assessment of reasonableness.
Keywords: Forensic Science; Digital Forensics; Evidence; Reasonable Line of Inquiry; Digital Investigation